Hummocky cross-stratification-like structures and combined-flow ripples in the Punta Negra Formation (Lower-Middle Devonian, Argentine Precordillera): A turbiditic deep-water or storm-dominated prodelta inner-shelf system? - Basilici, Giorgio (2012)
Turbidity-current and storm-induced deposits may exhibit similarities, in particularly when the latter is laid down by a combination of oscillatory and unidirectional flows. Recent progress in facies analysis helps to discriminate the sedimentary effects of oscillatory from unidirectional components of the flow. On the basis of detailed analysis of sedimentary facies, strata geometry, and palaeocurrent data, the present study reinterprets the Punta Negra Formation (PNF) (Lower-Middle Devonian, Argentine Precordillera), previously considered as a depositional system of deep-water, as a storm-dominated prodeltaic shelf depositional system.In the sandstone beds of the PNF, planar, low-angle and undulating laminations with weakly asymmetric hummocky and swaley bedforms, combined-flow ripples, accretionary hummocky cross-stratification-like (HCS-like), and anisotropic HCS-like suggest the action of oscillatory currents combined with unidirectional currents in forming the deposits. Different hypotheses on the origin of the oscillatory currents have been examined. The most convincing interpretation is that the oscillatory component of the velocity is attributed to storm-induced waves. The palaeocurrent data indicate offshore current directions, suggesting that the unidirectional flow was a gravity-induced bottom current. Inverse grading at the base and overlying normally graded divisions of the sandstone beds testify to waxing-waning behaviour of the depositional flows; interbedding of sedimentary structures (undulating laminations, low-angle and parallel laminations, and combined-flow ripples) in the lower and intermediate divisions of the beds indicate fluctuations of flow velocity. This organisation of the sedimentary structures permits association of the unidirectional component with hyperpycnal bottom currents. The terrestrial origin of the hyperpycnal flows is suggested by the abundance of terrestrial plant remains, the mineralogical and textural immaturity of the sandstone composition, and the relative scarcity of bioturbation, which was likely controlled by fresh-water input and a high rate of sedimentation. Storm-influenced, hyperpycnal flows generated subaqueous channelised forms at the mouth of the river deltas, which later filled with sand. At the distal end of the channelised forms, lobe-shaped sandstone beds were deposited, evolving distally into thin sandstone beds alternating with sandy mudstone. © 2012 Elsevier B.V.